Human Cytomegalovirus Stimulates Cellular IKK2 Activity and Requires the Enzyme for Productive Replication - Caposio, Patrizia (American Society for Microbiology, 2004)
Human cytomegalovirus (HCMV) exploits the host transcription factor NF-κB to enhance its own replication, dissemination, and reactivation from latency. Here we report that HCMV infection activates the upstream IκB kinase (IKK) complex and that its catalytic IKK2 subunit is required for HCMV-induced NF-κB activation, as well as the replication of different HCMV strains. These results indicate that IKK2 is essential for HCMV replication and emphasize the feasibility of blocking NF-κB activation as a way of inhibiting infection.